FACTORS AFFECTING THE COST OF DEBT IN CONSUMER GOODS INDUSTRY COMPANIES - Putri, Danisha Yoananda; Hafizi, Muhammad Riza; Wulandari, Diah (LP2M Universitas Bina Bangsa, 2024)
This research aims to analyze the influence of liquidity, institutional ownership, and tax avoidance on debt costs, both partially and simultaneously. The research method used in this research is a quantitative method with a comparative causal research type. The number of samples for this research is 14 samples obtained using a purposive sampling method from 75 populations of consumer goods industrial companies listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The data processing method uses multiple regression analysis with the SPSS 25 program. The research results show that liquidity has a negative and significant effect on the cost of debt, institutional ownership has a negative and significant effect on the cost of debt, and tax avoidance has a negative and significant effect on the cost of debt. Based on the F test, all independent variables, namely liquidity, institutional ownership, and tax avoidance, show a joint influence on the dependent variable, namely the cost of debt. Based on the results of the analysis, both partially and simultaneously liquidity, institutional ownership, and tax avoidance have a significant influence on the cost of debt in consumer goods industrial companies listed on the IDX in 2017-2021